Sensitivity Analysis for Frictional Contact Problems with Large Deformation - HISADA, Toshiaki; NAKAMURA, Kazuhiro; CHEN, Xian; MORI, Masahiko (Transactions of the Japan Society of Mechanical Engineers Series A, 1999)
Although the necessity of sensitivity analysis for frictional contact problems arises from many engineering fields, the research works have been rarely reported due to the complexity of the problems. In this paper, a sensitivity analysis approach for frictional contact problems with large deformation is presented. The continuum mechanics based formulation is carried out first and then a diseretized form is derived. The stick state is modeled by introducing a penalty type constraint. The unbalance force due to the variation of design parameters is evaluated numerically in the present sensitivity analysis method, thus the related routine of an existing FEM code can be utilized without paying an attention to the employed friction law. A couple of numerical examples including a realistic leaf spring problem are given to demonstrate the effectiveness of the proposed approach.